Evolution of surface O3 and PM2.5 concentrations and their relationships with meteorological conditions over the last decade in Beijing. (May 2015) - Zhang, Ziyin; Zhang, Xiaoling; Gong, Daoyi; Quan, Weijun; Zhao, Xiujuan; Ma, Zhiqiang; Kim, Seong-Joong
Abstract: In this study, hourly and daily records since 2005 and correlation, regression and composite methods were used to analyze the long-term evolution of surface O3 and PM2.5 concentrations at the rural station of Shangdianzi (SDZ) and urban station of Baolian (BL) over Beijing and their relationships with meteorological conditions. The results show that the mean concentrations of PM2.5 (O3 ) decreased (increased) at the urban and rural stations over the last decade. The linear trends of the annual mean concentrations of PM2.5 at BL and SDZ were −31.8 ug/m 3 /10yr (−4.3%/yr) (p < 0.01) and −13.3 ug/m 3 /10yr (−2.9%/yr) (p < 0.05), respectively. In winter, the mean wind speed ( W s ) and relative humidity ( RH ) were the most closely correlated with O3 at both stations, whereas RH and sunshine hours ( S ) were most closely correlated with PM2.5 . The correlation coefficients and explained variances in spring and autumn were generally less than those in winter and greater than those in summer. Moreover, increase in precipitation can significantly reduce the PM2.5 concentration in both urban and rural areas in Beijing, whereas trace and light precipitation more effectively decreases the O3 concentration. Concentrations of PM2.5 (O3 ) on haze days increased by 114% (3%) and 162% (20%) compared with that on non-haze days at the urban and rural stations, respectively. This result suggests that haze is a major manifestation of air pollution in Beijing. Highlights: PM2.5 (O3 ) concentrations decreased (increased) in Beijing over the last decade. Meteorological factors play important role in the daily variability of pollutants. Hazy days are a major manifestation of air pollution in Beijing.